Carbon dioxide assimilation, light use efficiency, growth and population dynamics in current soybean and maize genotypes - Sousa, Jackellyne Bruna (2020)
A factor that affects potential productivity is the environmental condition of the production environment, mainly the available solar radiation and, consequently, the air temperature. The use of solar radiation in soybean and maize crops was evaluated, especially in the spatial arrangement in maize (chapter I) and carbon assimilation in maize and soybean crops (chapter II). In chapter I was observed that: (i). for the maize hybrid BM 812PRO2 of early maturity and high yield potential, the increase of the plant population from 65,000 to 85,000 plants ha-1 (+30.1%) resulted in a yield decrease from 12.4 to 11.3 Mg ha-1 (-8.9%), indicating that the increase of plants ha-1 in relation to the recommended population of 65,000 plants ha-1 is not a viable practice; (ii). row spacings varying from 0.45 to 0.90 m did not interfere with yield, but 0.90 had a higher dry matter accumulation; (iii). a greater soil area occupied by one plant increased plant growth mainly during the reproductive growth period, improved solar radiation absorption through greater light extinction coefficient; and (iv). the beginning of the reproductive period was not affected by plant density and row spacing. In chapter II was observed that: (i). the proposed method for the determination of the Carbon Dioxide Assimilation gave good results for soybean and maize crops. The method is more complete and solid because it is based on the complete growth pattern of the cycle of the crops; (ii). soybean presented a greater efficiency of light and carbon use in relation to maize, grown under the same soil-water-climate conditions